John Constantine, Hellblazer. No future - Milligan, Peter (DC Comics, 2020)
"Constantine lives up to his true punk calling in No Future! Constantine reluctantly becomes embroiled in a group of anarchic punks who worship a powerful effigy of Sid Vicious. Complicating matters further is an alchemist and a violent group of extreme political fixers."--